2019
DOI: 10.1038/s41598-019-54655-4
|View full text |Cite
|
Sign up to set email alerts
|

Slot-Waveguide Silicon Nitride Organic Hybrid Distributed Feedback Laser

Abstract: One of the major barriers for a widespread commercial uptake of silicon nitride photonic integrated circuits for cost-sensitive applications is the lack of low-cost monolithically integrated laser light sources directly emitting into single-mode waveguides. In this work, we demonstrate an optically pumped organic solid-state slot-waveguide distributed feedback laser designed for a silicon nitride organic hybrid photonic platform. Pulsed optical excitation of the gain medium is achieved by a 450 nm laser diode.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 53 publications
2
12
0
Order By: Relevance
“…However, this did not represent a practical limitation in our experimentswe could test the SiNOH devices for several hours, i.e., with more than 100 000 pump pulses, while still retaining at least 50% of the initial emission power. These findings are in line with recently published results on similar devices [28] and should permit operation of SiNOH lasers in disposable point-of-care devices. Note that the pump pulse duration used in our experiments amounts to 20 ns and is thus significantly longer than the fluorescence lifetime of the dyes, which is approximately 5 ns [41].…”
Section: Comparative Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, this did not represent a practical limitation in our experimentswe could test the SiNOH devices for several hours, i.e., with more than 100 000 pump pulses, while still retaining at least 50% of the initial emission power. These findings are in line with recently published results on similar devices [28] and should permit operation of SiNOH lasers in disposable point-of-care devices. Note that the pump pulse duration used in our experiments amounts to 20 ns and is thus significantly longer than the fluorescence lifetime of the dyes, which is approximately 5 ns [41].…”
Section: Comparative Discussionsupporting
confidence: 92%
“…For the devices shown in this work, we use first-order Bragg gratings with a period of approximately 170 nm, which requires comparatively high lithography resolution. It has recently been demonstrated that SiNOH DFB lasers can also be realized with second-order gratings [27,28], having grating periods of more than 350 nm. Such structures are amenable to high-throughput mass fabrication using, e.g., 248 nm deep-UV lithography.…”
Section: Device Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…PhCs can be designed to exhibit a photonic bandgap (PBG) [10,11], low or zero group velocity slow-light [12][13][14][15], low effective volume (V eff ) confinement with high Q-factor [16][17][18], increased Purcell effect [19,20], orbital angular momentum [21], and transverse spin angular momentum [22]. There have been several demonstrations of PhC slot-waveguides [23,24] which have relied on slot widths >100 nm. There has been no demonstration of a PhC transverse-electric (TE) to transverse-magnetic (TM) polarization converter on an SOI platform.…”
Section: Introductionmentioning
confidence: 99%
“…Various dyes have been used for realizing fluidic or solid dye-lasers [ 1 , 2 , 3 ] by dissolving in organic solvents or doping in polymers. Compared with the fluidic dye-lasers, solid dye-lasers [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ] show more integration compatibilities with different optical platforms and photonic chips. To reduce the threshold and minimize the device footprint of this kind of dye-laser, the dye-doped polymer usually combines with the optical cavities [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ] based on different materials.…”
Section: Introductionmentioning
confidence: 99%